COPD maintenance medication is linked to left atrial size: Results from the COSYCONET cohort. (August 2021) - Kellerer, Christina; Kahnert, Kathrin; Trudzinski, Franziska C.; Lutter, Johanna; Berschneider, Korbinian; Speicher, Tim; Watz, Henrik; Bals, Robert; Welte, Tobias; Vogelmeier, Claus F.; Jörres, Rudolf A.; Alter, Peter
Abstract: Background: Lung function impairment in COPD is known to be related to reductions of left heart size, while short-term interventional trials with bronchodilators showed positive effects on cardiac parameters. We investigated whether COPD maintenance therapy has analogous long-term effects. Methods: Pooled data of GOLD grade 1–4 patients from visits 1 and 3 (1.5 y apart) of the COSYCONET cohort were used. Medication was categorized as use of ICS, LABA + ICS, LABA + LAMA and triple therapy (LABA + LAMA + ICS), contrasting "always" versus "never". Echocardiographic parameters comprised left ventricular end-diastolic and -systolic diameter (LVEDD, LVESD), ejection fraction (LVEF) and left atrial diameter (LA). Associations were identified by multiple regression analysis, as well as propensity score analysis. Results: Overall, 846 patients (mean age 64.5 y; 41% female) were included, 53% using ICS at both visits, 51% LABA + ICS, 56% LABA + LAMA, 40% LABA + LAMA + ICS (triple) therapy. Conversely, 30%, 32%, 28% and 42% had no ICS, LABA + ICS, LABA + LAMA or triple therapy, respectively, at both visits. Among echocardiographic measures, only LA showed statistically significant associations (increases) with medication, whereby significant effects were linked to ICS, LABA + ICS and LABA + LAMA (p < 0.05 each, "always" versus "never") and propensity score analyses underlined the role of LABA + LAMA. Conclusions: In this observational study, COPD maintenance therapy, especially LABA + LAMA, was linked to left atrial size, consistent with the results of short-term interventional trials. These findings suggest that maintenance medication for COPD does not only improve lung function and patient reported outcomes but may also have an impact on the cardiovascular system. Trial registration: NCT01245933 Highlights: To investigate long-term effects of COPD maintenance medication on cardiac size and function in an observational COPD cohort. Long-term respiratory therapy with ICS, LABA + ICS and particularly LABA + LAMA had effects on the left atrial diameter. COPD maintenance medication not only improves lung function, but also may have beneficial effects on the heart.